Metal–organic framework-based foams for efficient microplastics removal. Issue 29 (15th July 2020) - Chen, Yong-Jun; Chen, Yifa; Miao, Chang; Wang, Yi-Rong; Gao, Guang-Kuo; Yang, Ru-Xin; Zhu, Hong-Jing; Wang, Jian-Hui; Li, Shun-Li; Lan, Ya-Qian
Abstract : Zirconium metal–organic frameworks based foam materials have been successfully fabricated and applied in microplastic removal with high efficiency. Abstract : Microplastics are a worldwide problem that poses a giant threat to organisms in the ecosystem and even to human health. The removal of microplastics is a severe challenge that needs to be solved urgently. Herein, a series of zirconium metal–organic framework-based foam materials with interpenetrated pores, high MOF uniformity and excellent durability have been successfully fabricated and applied in simulated microplastics removal in water or seawater conditions. They can be applied to various types and concentrations of microplastics suspensions. It is worth noting that the best of them, UiO-66-OH@MF-3, can efficiently remove microplastics with an efficiency of up to 95.5 ± 1.2% and can maintain high performance in recycling and large-quantity filtration experiments. Besides, we proposed an automatic filtration system powered by sunlight and accomplished it on the lab-scale. The high performances of these foam materials combined with the new concept of automatic filtration systems might shed some light on the development of novel techniques for microplastics removal.